Nilai-Nilai Filosofi Kehidupan Dalam Geguritan Jayaprana - Nyoman Suardika (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2021)
Literary work is a work that contains values and teachings that can serve as a guide for life. A literary work, especially an old (traditional) literary work, is usually regional in nature or still contains local culture in its creation. One example of an old (traditional) literary work is Geguritan Jayaprana. This type of research used in this research is descriptive with a qualitative approach. The data source of this research is primary data or data obtained directly from the original source, namely the transcription book Geguritan Jayaprana by Ketut Ginarsa. Data collection was carried out by reading repeatedly on the object of research. The results showed that the formal structure analysis includes language and literature codes, language styles, and language varieties. The philosophical values of life there are several stories in the geguritan verse that describe the attitude or behavior of Jayaprana who is always loyal to his king to sacrifice anything for his king, even if it hurts him and even his life. This was done by Jayaprana to repay the king's kindness to him. Besides that Jayaprana is a person who really respects others.